PENGELOLAAN LIMBAH B3 PT YTK Indonesia - Nisa Nurhidayanti; Cici Arinih (DPPM Universitas Pelita Bangsa, 2019)
PT. YTK Indonesia is one of the automotive industries in Indonesia that does not yet have a permit related to processing hazardous and toxic waste, so that the resulting hazardous and toxic waste is handed over to third parties for further processing. The presence of hazardous and toxic waste produced from various production activities requires special attention, because the losses that will be caused if the waste is not managed and not properly treated. The purpose of this study was to determine the type of hazardous and toxic waste and hazardous and toxic management produced and to assess the suitability of hazardous and toxic waste management with Government Regulation No. 101 of 2014. Data analysis was carried out by conducting a literature study of the research objects and basic concepts of hazardous and toxic waste management systems. hazardous and toxic wastes produced are used drums, used buckets, contaminated mounds, contaminated cloth gloves, iron scrab, grinding sludge, contaminated wood powder, aluminum powder, NG parts, waste material, contaminated gloves, used oil, and domestic hazardous and toxic waste. Hazardous and toxic waste Management carried out includes reduction, storage, storage, internal transportation, external transportation and utilization. The processing of hazardous and toxic waste is left to a third party, namely PT. Menembus Batas Langit and PT. Karya Nusa Bumi Persada. All hazardous and toxic waste management processes at PT. YTK Indonesia as a whole has complied with government regulations, but there is a discrepancy with PP No. 101 of 2014 which is about hazardous and toxic waste packaging that does not have labels and symbols and there is a storage area for hazardous and toxic waste that has rust.